The Causes and Consequences of Differing Pensions Accounting Assumptions in UK Pension Schemes - Thomas, Gareth (2006)
Anecdotal evidence and a number of empirical studies from the US suggest that the providers of corporate pension schemes may manipulate the actuarial assumptions used to estimate the value of the scheme. By manipulating the pension scheme assumptions corporations can reduce their required contribution to the scheme in order to manage their perceived performance. A sample of 92 FTSE 100 companies during the period 2002-2004 was taken and the link between corporate financial constraint and pension assumptions was analysed. The results provide some evidence that the firms in the sample may have used the estimate of salary growth rate to reduce their measured pension liability during the period. The link between the assumptions and the liabilities themselves suggests that the current reporting standards fail to provide adequate information to the users of accounts. The results also suggest that at any given point in time a high proportion of equity is associated with a lower pension ratio. The inclusion of mortality assumptions and information about the maturity of the scheme are recommended, as is increased transparency in the assumption setting process. The research provides a platform for further empirical investigation and suggests a number of potentially appealing directions for future study.